Integrasi Storytelling dan Media Audio-visual untuk Menanamkan Nilai-Nilai Moderasi Beragama pada Anak Usia Dini - Eka Restuti Munawir, A. Nidha (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study investigates the effectiveness of integrating storytelling activities with audio-visual media to instill religious moderation values in early childhood. Using a pre-experimental quantitative approach with a one-group pre-test–post-test design, the research involved 20 Group A children at Alam Insan Madani Kindergarten, Bulukumba Regency. Data were collected through participatory observation before and after the intervention and analyzed using descriptive statistics and a paired t-test. The results revealed a significant improvement in children’s understanding of religious moderation values, with mean scores rising from 26.50 (pre-test) to 41.80 (post-test); the paired t-test confirmed this effect as statistically significant (p < 0.001). These findings indicate that integrating storytelling with audio-visual media provides an effective and enjoyable approach to fostering tolerance, cooperation, empathy, and respect for diversity among young learners